2019
DOI: 10.1037/amp0000438
|View full text |Cite
|
Sign up to set email alerts
|

Who watches an ISIS beheading—And why.

Abstract: In the wake of collective traumas and acts of terrorism, media bring real graphic images and videos to TV, computer, and smartphone screens. Many people consume this coverage, but who they are and why they do so is poorly understood. Using a mixed-methods design, we examined predictors of and motivations for viewing graphic media among individuals who watched a beheading video created by the terrorist group Islamic State of Iraq and Syria (ISIS). A representative national sample of U.S. residents (N = 3,294) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 44 publications
(62 reference statements)
0
15
1
Order By: Relevance
“…Our prediction is at odds with Redmond et al’s (2019) finding that fear of terrorism was associated with a greater likelihood of having seen a beheading video in 2015. The researchers fail to measure anger, however, which is positively related to fear in self-report data.…”
contrasting
confidence: 72%
“…Our prediction is at odds with Redmond et al’s (2019) finding that fear of terrorism was associated with a greater likelihood of having seen a beheading video in 2015. The researchers fail to measure anger, however, which is positively related to fear in self-report data.…”
contrasting
confidence: 72%
“…Finally, many individuals voluntarily choose to expose themselves to extensive media coverage of mass events that may include bloody images (see Redmond, Jones, Holman, & Silver, 2019), suggesting the potential for an unmeasured, individual difference variable (e.g., neuroticism) to operate as a potential third variable linking media exposure with the mental-health outcomes we measured. Although we acknowledge this possibility, we note that we have controlled for several likely third variables (prior mental health, direct BMB exposure, demographics) that may provide alternative explanations for our results.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should examine patterns of media consumption during and immediately following collective trauma and identify who is most vulnerable to this exposure, their motivations for viewing graphic media coverage (see Redmond et al, 2019), and the specific qualities of media coverage most closely associated with mental-health outcomes. For example, collecting and/or experimentally manipulating fine-grained qualities of media coverage (e.g., sounds such as hearing gunshots, screaming victims) would allow more careful analysis and identification of specific emotional triggers and in so doing provide information that more easily translates to interventions and guidance for media.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, those who chose to view the drama were more likely to have experienced posttraumatic stress reactions before they viewed the show. Likewise, Redmond, Jones, Holman, and Silver (2019) found that among a representative sample of U.S. residents, a history of violent victimization was associated with a higher likelihood of watching a graphic beheading video made by the terrorist group Islamic State of Iraq and Syria. Notably, these behaviors do not appear to produce habituation of distress provoked by triggering cues in case or empirical studies.…”
mentioning
confidence: 96%